2019
DOI: 10.1177/1756286419859722
|View full text |Cite
|
Sign up to set email alerts
|

Advances in brain imaging in multiple sclerosis

Abstract: Brain imaging is increasingly used to support clinicians in diagnosing multiple sclerosis (MS) and monitoring its progression. However, the role of magnetic resonance imaging (MRI) in MS goes far beyond its clinical application. Indeed, advanced imaging techniques have helped to detect different components of MS pathogenesis in vivo, which is now considered a heterogeneous process characterized by widespread damage of the central nervous system, rather than multifocal demyelination of white matter. Recently, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 123 publications
2
45
0
6
Order By: Relevance
“…Indeed, Tataroglu et al [85] found that sensitivity and specificity of CMCT, CSP, and MEPs were up to 89.7% and 96.7%, respectively, suggesting that TMS may be useful to rule out MS in a healthy person under investigation [110]. These values are similar for other biomarkers under development such as NfL (sensitivity: 89.5%, specificity: 95.4%) [32], while other modalities such as MRI are suggested to lack the sensitivity and specificity required for a valid screening tool [29]. Others have likewise suggested that TMS is a useful candidate screening tool for MS, with a sensitivity up to 93% [24, 35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, Tataroglu et al [85] found that sensitivity and specificity of CMCT, CSP, and MEPs were up to 89.7% and 96.7%, respectively, suggesting that TMS may be useful to rule out MS in a healthy person under investigation [110]. These values are similar for other biomarkers under development such as NfL (sensitivity: 89.5%, specificity: 95.4%) [32], while other modalities such as MRI are suggested to lack the sensitivity and specificity required for a valid screening tool [29]. Others have likewise suggested that TMS is a useful candidate screening tool for MS, with a sensitivity up to 93% [24, 35].…”
Section: Discussionmentioning
confidence: 98%
“…Differentiation between relapsing-remitting (RRMS) and progressive subtypes of MS—disease stages with markedly different pathophysiology [2]—is based almost solely on clinical features, and few reliable biomarkers of disease progression have been established to help guide treatments [26, 27]. Nevertheless, several prospective modalities are under continuing evaluation and validation, including magnetic resonance imaging (MRI) [28, 29], optical coherence tomography (OCT) [30], corticospinal fluid (CSF) parameters [31], and neurofilament light chain (NfL) analyses [32]. Alternatively, some work has argued that TMS may be ideally suited as a surrogate marker for MS [3335].…”
Section: Introductionmentioning
confidence: 99%
“…(dissémination temporelle). Ces études d'imagerie cérébrale ont un rôle fondamental en terme de diagnostic, mais aussi pour le pronostic et l'évaluation de la réponse au traitement [8]. L'analyse du liquide céphalo-rachidien permet, elle, la recherche (en western blot) de bandes oligoclonales d'immunoglobulines.…”
Section: La Sclérose En Plaquesunclassified
“…11c). Bei höheren Feldstärken und der Kombination aus einer FLAIR-Sequenz mit zusätzlicher Suszeptibilitätswichtung (FLAIR*) ist die perivenöse Lokalisation der Plaqueskorrelierend zur histologischen Beschreibungmitunter gut zu erkennen [3,5,6,14]. "Red flags" sind dagegen […”
Section: Periventrikuläre Läsionunclassified
“…Die differenzialdiagnostische Abgrenzung zu erregerassoziierten und anderen autoimmun bedingten Entzündungen wie auch zu neoplastischen Entitäten ist insbesondere zum Zeitpunkt der ersten Untersuchung mitunter schwierig. Hier sind kurzfristige Verlaufsuntersuchungen hilfreich [14]. Auch wenn zunächst nur ein monophasischer und bildgebend monomorpher Befund vorliegt, geht die Erkrankung im Verlauf von 5 Jahren in etwa 30-60 % in eine MS über [7,32].…”
Section: Differenzialdiagnose Der Msunclassified